2023
DOI: 10.1371/journal.ppat.1011307
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and chikungunya virus loads in the mosquito Aedes aegypti are determined by distinct genetic architectures

Abstract: Aedes aegypti is the primary vector of the arboviruses dengue (DENV) and chikungunya (CHIKV). These viruses exhibit key differences in their vector interactions, the latter moving more quicky through the mosquito and triggering fewer standard antiviral pathways. As the global footprint of CHIKV continues to expand, we seek to better understand the mosquito’s natural response to CHIKV—both to compare it to DENV:vector coevolutionary history and to identify potential targets in the mosquito for genetic modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…In contrast, there was a moderate salivary gland escape barrier when mosquitoes were infected with ZIKV or CHIKV but not DENV. The influence of genetic factors was also more pronounced when viral titers were low (Novelo et al, 2023). Taken together, mounting evidence supports an underlying genetic basis for VC, but that is variable across mosquito and virus species.…”
Section: Salivary Glandsmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, there was a moderate salivary gland escape barrier when mosquitoes were infected with ZIKV or CHIKV but not DENV. The influence of genetic factors was also more pronounced when viral titers were low (Novelo et al, 2023). Taken together, mounting evidence supports an underlying genetic basis for VC, but that is variable across mosquito and virus species.…”
Section: Salivary Glandsmentioning
confidence: 79%
“…Even within the same isofemale line (family), mosquito genetic background may be influencing VC for different viruses in disparate ways. Novelo et al investigated the impact of genetic variation on VC for DENV and CHIKV by employing a modified full-sibling design using viral RNA quantity as a proxy value for VC (Novelo et al, 2023). Mosquitoes from 37 families were reared separately; half of the siblings from each family were challenged with CHIKV and the other half DENV.…”
Section: Mosquito Genotype Influencesmentioning
confidence: 99%
“…In Brazil, the main vectors associated with the transmission of these CHIKV lineages are the mosquitoes Aedes aegypti and Aedes albopictus , both of which are widely distributed across the country [ 7 ]. Previous studies have shown that these two Aedes species are competent vectors for both the ECSA and Asian lineages across different regions of the world [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, in Brazil, the impact of locally circulating CHIKV genotypes and specific combinations of local Aedes aegypti populations on the vector competence has not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the main vectors associated with the transmission of these CHIKV lineages are the mosquitoes Aedes aegypti and Aedes albopictus, both of which are widely distributed across the country [14,18,20,29]. Previous studies have shown that these two Aedes species are competent vectors for both the ECSA and Asian lineages across different world regions [15,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%